Spatially resolved optical emission of cubic GaN/AlN multi-quantum well structures. Issue 1736 (19th December 2014) - As, D.J.; Kemper, R.; Mietze, C.; Wecker, T.; Lindner, J.K.N.; Veit, P.; Dempewolf, A.; Bertram, F.; Christen, J.
ABSTRACT: In this contribution we report on the optical properties of cubic AlN/GaN asymmetric multi quantum wells (MQW) structures on 3C-SiC/Si (001) substrates grown by radio-frequency plasma-assisted molecular beam epitaxy (MBE). Scanning transmission electron microscopy (STEM) and spatially resolved cathodoluminescence (CL) at room temperature and at low temperature are used to characterize the optical properties of the cubic AlN/GaN MQW structures. An increasing CL emission intensity with increasing film thickness due to the improved crystal quality was observed. This correlation can be directly connected to the reduction of the linewidth of x-ray rocking curves with increasing film thickness of the c-GaN films. Defects like stacking faults (SFs) on the 111 planes, which also can be considered as hexagonal inclusions in the cubic crystal matrix, lead to a decrease of the CL emission intensity. With low temperature CL line scans also monolayer fluctuations of the QWs have been detected and the observed transition energies agree well with solutions calculated using a one-dimensional (1D) Schrödinger-Poisson simulator.